“Aspectos epidemiológicos del parto de pretérmino en el hospital II IPSS Tarapoto 1,989 – 1,993” - Navarro Torres, María Antonieta (1994)
In hospital II IPSS - Tarapoto in the period comprised 1,989 - 1,993, there were a total of 8,699 deliveries, of which 676 were preterm deliveries with an average incidence of 7.8%. Among the demographic characteristics, it was found that the patients had an average age of 25.33 years, came from the urban area, with secondary education, married civil status, multiparous women, domestic workers and with an intergenesico period less or equal to 2 years. In terms of maternal history and associated pathologies, abortion and preterm delivery predominated in the first, and in the second, RPM and UTI predominated in the sample. 56.21% had ANC, with an average hemoglobin of 10.97 Gr. Only 9.9% of all patients received tocolytics, the most used drug being the Dilator. The most common way of delivery was vaginal (80.51%), followed by abdominal (19.49%); Cephalic fetal presentation (77.78%) and fetal fetal presentation predominated (18,255). In the characteristics of the newborn, the male gender (52.65%) had a mean gestational age of 33.17 weeks, an average weight of 1.755 gr. And an average APGAR per minute of 7, 6 points. On the other hand, maternal morbimortality was studied, with carioamnionitis (5.1%) and endometritis (4.8%) being the main causes of morbidity. There were no cases of specific maternal death due to prematurity. Regarding perinatal morbidity and mortality, the main causes of extreme prematurity and sepsis